Motherhood choice in multiple sclerosis (MoMS) – Pilot trial of web-based decision support - Lara S. Stahl; Julia Hickstein; Sascha Köpke; Kerstin Hellwig; Christoph Heesen; Anne C. Rahn (PLoS ONE, 2026)
Backgroud Uncertainty concerning motherhood is common among women with multiple sclerosis (wwMS). Therefore, we developed and pre-tested a patient decision aid (PtDA) and a nurse-led decision coaching intervention (DC) to support motherhood choice. The DC includes the PtDA, a decision guide on motherhood choice, and decision coaching. Methods We conducted a randomised pilot trial across Germany to test feasibility, with decisional conflict (Decisional Conflict Scale, DCS) as an exploratory endpoint. Initially, we planned a 3:1 randomisation ratio (planned; PtDA = 48, DC = 16). Due to recruitment difficulties, we switched to a 1:1 randomisation ratio to ensure an appropriate sample size (PtDA > 20, DC > 10). Women between 18 and 45 years old with relapsing-remitting MS or clinically isolated syndrome, and who had not yet decided about motherhood, were eligible. We recruited two nurses for our decision coaching training course. We used questionnaires to measure decisional conflict, programme feasibility, knowledge, and worries regarding pregnancy in MS. Interviews were conducted to gain in-depth information on the potential feasibility of the programmes. Interviews were analysed thematically and questionnaires descriptively. We conducted explorative group comparisons and merged findings using joint display analysis. Results We trained two decision coaches in the DC group and recruited 35 wwMS (PtDA = 22; DC = 13) over five months. Median DCS scores in the DC group were 49 at baseline and 15 at follow-up (range 0–100; higher scores indicate greater decisional conflict). In the PtDA group, scores were 54 (baseline) and 31 (follow-up). Explorative group comparison indicated lower decisional conflict at follow-up in the DC group than in the PtDA group (p = 0.035). Interviewees (PtDA = 5; DC = 6; nurses = 2) described both interventions as helpful for decision-making. Qualitative findings indicate greater satisfaction levels in the DC group. Conclusion Both interventions appear useful for wwMS in making motherhood choices. The DC programme seems more promising in supporting decision-making. Trial registration German Clinical Trials Register (DRKS); DRKS00038534.